On the Search for Grazing Personalities: From Individual to Collective Behaviors - Moreno García, Cristian A.; Maxwell, Thomas M. R.; Hickford, Jonathan; Gregorini, Pablo (Frontiers in Veterinary Science, 2020)
We picture foraging animals distributed throughout grazing lands. Individually or in various sized groups of one or more species, herbivores explore and graze a diverse range of habitats. While grazing lands can offer a diverse range of forage, individuals within herds prefer to graze some habitats and not others. They can have consistent differences in grazing patterns and occupy specific spatial domains, whilst developing tactics and strategies for foraging that are specific to their grazing personalities. In this review, we explore the development of our understanding of ruminant grazing personalities, as we move away from the search for an ‘optimal animal’ towards designing ruminant herds with an arrangement of individual grazing personalities that enhance ecosystem services and productivity. We present a ‘grazing personality model’ that account for the personality of individual animals and also for collective behaviors in herds. We argue that ruminant grazing personalities are in part genetically determined, and that they can act at the individual and collective level. The social and biophysical environments as well as the emotional state of animals regulate the expression of ‘grazing genes’ that are observed phenotypically as distinct grazing personalities. The reproductive success of individuals and collective herds filters the allele variants of grazing genes and in turn determines their relative frequency. While the selection of one grazing personality may be adequate for homogeneous pastoral systems, the design of herds with a range of grazing personalities that are matched to the habitat diversity may be a better approach to improving the distribution of grazing ruminants, enhancing their ecosystem services and maximizing productivity.